Structural host responses of Acacia mangium and Eucalyptus pellita to artificial infection with the root rot pathogen, Ganoderma philippii. Issue 4 (21st June 2016) - Gill, W.; Eyles, A.; Glen, M.; Mohammed, C.
Summary: Structural host responses of young Acacia mangium and Eucalyptus pellita to infection with the root rot pathogen Ganoderma philippii were described. To our knowledge, this is the first report investigating the histology of root responses infected with G. philippii . The infected roots of A. mangium were characterized by the presence of a continuous multilayered mycelial sheath ( 100–200 μm thick), fungal outgrowths and the production of a wound periderm. In contrast, roots of E. pellita were characterized by a mycelial sheath and fungal outgrowths and a wound periderm comprising of only one to four rows of cells.